Indonesia's Diplomatic Challenges in Responding to Nuclear-Based Military Modernization Plans in the Indo-Pacific Region - Elok, Salsabil; Darmawan, Waean Budi; Sudirman, Arifin (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The Indo-Pacific region has emerged as a focal point of geopolitical tensions, primarily driven by advancements in nuclear military capabilities. This is particularly evident in the context of the AUKUS partnership, which facilitates the transfer of nuclear-powered submarine technology to Australia. Indonesia, known for its non-nuclear stance and active participation in ASEAN, has diligently worked to promote denuclearization and strengthen regional stability through multilateral diplomatic efforts on platforms such as ASEAN, the IAEA, and the Non-Aligned Movement. This analysis explores the complexities Indonesia faces in its endeavors, emphasizing the role of multilateral diplomatic strategies in addressing the nuances of nuclear-based military modernization. Employing a qualitative methodology focused on document analysis, the study reveals that Indonesia encounters several challenges, including major power rivalries, conflicting interests within ASEAN, and limited diplomatic resources. The article argues that multilateral diplomacy serves as a strategic pathway for Indonesia to advance peace in the Indo-Pacific, although it requires careful navigation of intricate geopolitical dynamicst.